2005
DOI: 10.1016/j.bbamcr.2005.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Rapid inhibition of MAPK signaling and anti-proliferation effect via JAK/STAT signaling by interferon-α in hepatocellular carcinoma cell lines

Abstract: The potential anti-proliferation effect of interferon-alpha (IFN-alpha) against hepatocellular carcinoma (HCC) and its growth inhibitory mechanisms remain unclear. We examined four human HCC cell lines and every cell line had the anti-proliferative effect of IFN-alpha. The PLC/PRF/5 cell line, which expressed the IFN receptor most abundantly, responded most effectively to IFN-alpha stimulation. Here, we delineate the anti-proliferative effect of IFN-alpha via the MAPK pathway in human HCC cell lines. IFN-alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…In a hepatocellular carcinoma cell (HCC) study, JAK/STAT activated by interferon-α inhibited MAPK signalling by cross-talking with MEK/ERK pathway (36). Our results in sarcoma suggest this may be due to IFNα induced alteration of the balance between STAT1 and STAT3/ STAT5 favouring inhibition of proliferation and subsequent apoptosis (37).…”
Section: Biology Of Stat3mentioning
confidence: 56%
“…In a hepatocellular carcinoma cell (HCC) study, JAK/STAT activated by interferon-α inhibited MAPK signalling by cross-talking with MEK/ERK pathway (36). Our results in sarcoma suggest this may be due to IFNα induced alteration of the balance between STAT1 and STAT3/ STAT5 favouring inhibition of proliferation and subsequent apoptosis (37).…”
Section: Biology Of Stat3mentioning
confidence: 56%
“…Cells (7x10 5 ) were harvested at indicated times and lysed with lysis buffer containing 1% Triton X-100, 50 mM Tris (pH 7.5), 10 mM EDTA, 0.02% NaN 3 , and protease inhibitor cocktail (Sigma-Aldrich). The membrane (Millipore, Billerica, MA, USA) was blocked with 5% skim milk in TBS-T [50 mM Tris, 150 mM NaCl and 0.05% Tween-20, (pH 7.6)] at room temperature for 1 h and probed with primary antibodies at 4˚C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Cells (7x10 5 ) were treated with GW6471 or fludarabine for 1 h before IFN-α and fluoxetine, and then harvested at day 1 for performing ICE-family proteases/ caspases activation to initiate apoptosis. The caspase-3/CPP32 colorimetric assay kit (BioVision, Inc., Milpitas, CA, USA) was used according to the manufacturer's protocols and measured with a spectrophotometer at 405 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data demonstrate that overexpressing the LKB1 gene inhibits the activation of ERK1/2 and STAT3 proteins in the transfected A549 cells. Some studies demonstrated that one of the subtypes of MAPK could phosphorylate STAT3, which suggested cross-talk between MAPK cascades and JAK-STAT pathways (24,30). It is also now clear that the cross-talk of these pathways contributes to the final proliferation effect on target cells by promoting G1-S phase cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%